2000
DOI: 10.1046/j.1464-410x.2000.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative simulation of partial nephrectomy with three‐dimensional computed tomography

Abstract: Objective To evaluate prospectively the accuracy of computer-aided three-dimensional (3D) volumerendered computed tomography (CT) in determining the appropriate anatomical limits (tumour size, tumour location, multifocality and vascular supply) and as a potential tool in the preoperative simulation of nephron-sparing surgery (NSS) in patients with small-volume renal cell carcinoma (RCC). Patients and methods The study included 36 patients who underwent transperitoneal radical nephrectomy for RCC of <4 cm diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…They showed that 3-D CT could accurately identify the tumor characteristics and vascular system anatomy. Of 39 renal tumors and 43 renal arteries, only three tumors, each of which measured less than 4 mm, and one accessory renal artery were not identified preoperatively [33]. Similar results were reported by Coll et al on 60 patients evaluated with 3-D rendered CT before PN.…”
Section: -D Imagingsupporting
confidence: 82%
“…They showed that 3-D CT could accurately identify the tumor characteristics and vascular system anatomy. Of 39 renal tumors and 43 renal arteries, only three tumors, each of which measured less than 4 mm, and one accessory renal artery were not identified preoperatively [33]. Similar results were reported by Coll et al on 60 patients evaluated with 3-D rendered CT before PN.…”
Section: -D Imagingsupporting
confidence: 82%
“…The corticomedullary phase is used to assess the arterial system (number of renal arteries, feeding mass arteries) and the urographic phase to assess proximity to and involvement of the renal collecting system [14]. Three-dimensional CT reconstruction depicts the vascular and renal mass anatomy in a format familiar to surgeons and serves to guide PN surgery, especially in complex cases [15,16]. …”
Section: Evidence Synthesismentioning
confidence: 99%
“…3D‐CT angiography has been used as a tool for the preoperative evaluation of NSS . Computer simulation with 3D reconstruction of kidney, including the tumor, vasculature, and renal hilum, has allowed a significantly better preoperative evaluation of the renal mass …”
Section: Discussionmentioning
confidence: 99%
“…9 Computer simulation with 3D reconstruction of kidney, including the tumor, vasculature, and renal hilum, has allowed a significantly better preoperative evaluation of the renal mass. 10 The incorporation of 3D printing to develop simulation models and training devices for surgical education may prove to be a valuable resource to oncological pediatric surgery trainees. 11 3D technology can provide a topographical map of the kidney surface and complete views of intrarenal anatomy.…”
Section: Discussionmentioning
confidence: 99%